Choroidal profile in patients with inactive thyroid-associated ophthalmopathy - Mahsan Samadi; Hamidreza Ghanbari; Ali Momeni; Elias Khalili Pour; Ali Banafsheh Afshan; Nima Naghshtabrizi; Seyed Mohsen Rafizadeh; Hamid Riazi Esfahani (BMC Ophthalmology)
Abstract Background Thyroid associated ophthalmopathy (TAO) is a common autoimmune condition affecting orbital tissues. In this study, we aim to explore the alterations in choroidal vasculature during inactive phases of TAO by assessing choroidal vascularity index (CVI) and subfoveal choroidal thickness (SFCT) in these patients. Methods In this cross-sectional comparative case series, enhanced-depth imaging optical coherence tomography (EDI-OCT) images were utilized to compare SFCT and CVI between patients with inactive TAO and age- and sex-matched normal individuals. For CVI assessment, foveal scans underwent binarization using the ImageJ software, with calculations based on the ratio of c (LA) to total choroidal area (TCA). Additionally, we investigated the associations between SFCT or CVI and factors such as age, gender, clinical activity score (CAS), proptosis, duration of disease, and margin to reflex distance (MRD). Results The study included 50 eyes of 37 patients with inactive TAO (mean ± standard deviation (SD) age: 47 ± 11 years) and 282 eyes of 141 healthy individuals (mean ± SD age: 61 ± 11 years). SFCT and CVI were significantly higher in the TAO group compared to the control group (409.5 ± 152.7 μm vs. 249.3 ± 71.2 μm and 0.684 ± 0.037 vs. 0.629 ± 0.038, p < 0.001 for both). There was a significant negative association between age and SFCT in both univariate and multivariate analysis (r = -0.392, p = 0.003 and β = -0.04, p < 0.001, respectively). In multivariate analysis, we also noted a significant negative association between age and CVI (β = -0.09, p < 0.001). Apart from the correlation between MRD2 and SFCT (r = 0.297, p = 0.038 in univariate analysis and β = 38.15, p = 0.028 in multivariate analysis), no significant associations were observed between CVI or SFCT and clinical parameters in the TAO group (p > 0.05). Conclusions SFCT and CVI were significantly higher in the inactive TAO group compared to healthy controls. Although SFCT was significantly affected by age, no relationship was observed between CVI and physiologicical or disease-related parameters in univariate analysis. These findings accentuate the complexity of choroidal remodeling in TAO and emphasize the multifactorial nature of its pathogenesis. Further investigations are warranted to elucidate the underlying mechanisms driving these observed alterations and their clinical implications in managing individuals with TAO.